2012
DOI: 10.1186/1752-1947-6-169
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of stage IV idiopathic full-thickness macular hole and late reopening as a lamellar macular hole: a case report

Abstract: Introduction Spontaneous closure of traumatic macular holes is described as a common event in the peer-reviewed literature. However, the spontaneous closure of stage III and IV full-thickness idiopathic macular holes has been reported in less than 15 cases in the literature, this being an extremely rare event, with their reopening being even more infrequent. We report a case of a spontaneous closure of stage IV idiopathic full-thickness macular hole and late reopening as a lamellar macular hole. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…In our review data, the diameter of 34 IMHs are smaller than 250 μ m and that in 13 IMHs are between 250 μ m and 400 μ m. It seems that the small diameter of IMHs gives the chance to both edges of the IMHs to combine together. Also, in a case studied by Fernández and Navarro [ 10 ], the minimum diameter of IMHs is much smaller than basal diameter. They suggested that this may be a recovery phenomenon, which indicates the inner layer of macular retinal concentrates to the center.…”
Section: Imh Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…In our review data, the diameter of 34 IMHs are smaller than 250 μ m and that in 13 IMHs are between 250 μ m and 400 μ m. It seems that the small diameter of IMHs gives the chance to both edges of the IMHs to combine together. Also, in a case studied by Fernández and Navarro [ 10 ], the minimum diameter of IMHs is much smaller than basal diameter. They suggested that this may be a recovery phenomenon, which indicates the inner layer of macular retinal concentrates to the center.…”
Section: Imh Diametermentioning
confidence: 99%
“…It is widely believed that spontaneous release of the vitreomacular traction (VMT) may account for the closure of IMHs [ 21 ], which is also the theory of vitrectomy surgery, since many MHs closed after the relieve of VMT [ 5 , 6 , 8 10 ]. Indeed, in our review data, more than half of the IMHs were in stage II, and most VMT relieve during their spontaneous closure of IMHs.…”
Section: Vmtmentioning
confidence: 99%
“…Three months after the presentation, they observed that the hole spontaneously closed, however two years later it reopened as a lamellar macular hole. [ 10 ] To the best of our knowledge, our case is the first report decribing the epiretinal proliferation tissue associated with macular hole which spontaneously closed and reopened as a LMH, and spontaneous full anatomical closure of the whole hole cavity with EP tissue.…”
Section: Discussionmentioning
confidence: 90%
“…However, late reopening as a LMH is an extremely rare situation. [ 10 ] Previously, Garcia Fernandez et al . defined a case with a stage IV full-thickness idiopathic macular hole and a small epiretinal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous closure of idiopathic full thickness macular hole secondary to release of VMT has been reported (Scassa et al 2011) and associated with Posterior vitreous detachment (PVD) (Milani et al 2007, García Fernández & Castro Navarro 2012. The case was rare and the base of the macular hole was less than 500 μm.…”
Section: Introductionmentioning
confidence: 98%